Establishment of Chronic Infection: Brucella's Stealth Strategy - Ahmed, Waqas; Zheng, Ke; Liu, Zheng-Fei (Frontiers in Cellular and Infection Microbiology, 2016)
Brucella is a facultative intracellular pathogen that causes zoonotic infection known as brucellosis which results in abortion and infertility in natural host. Humans, especially in low income countries, can acquire infection by direct contact with infected animal or by consumption of animal products and show high morbidity, severe economic losses and public health problems. However for survival, host cells develop complex immune mechanisms to defeat and battle against attacking pathogens and maintain a balance between host resistance and Brucella virulence. On the other hand as a successful intracellular pathogen, Brucella has evolved multiple strategies to evade immune response mechanisms to establish persistent infection and replication within host. In this review, we mainly summarize the “Stealth” strategies employed by Brucella to modulate innate and the adaptive immune systems, autophagy, apoptosis and possible role of small noncoding RNA in the establishment of chronic infection. The purpose of this review is to give an overview for recent understanding how this pathogen evades immune response mechanisms of host, which will facilitate to understanding the pathogenesis of brucellosis and the development of novel, more effective therapeutic approaches to treat brucellosis.